1997
DOI: 10.1021/jp9711959
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an Adsorbed Layer of n-Dodecyl-N,N-dimethylamino Acetate at the Air/Solution Interface As Determined by Neutron Reflection

Abstract: The composition and structure of the interfacial layer formed at the air/water interface by a zwitterionic surfactant, n-dodecyl-N,N-dimethylamino acetate, has been determined by neutron reflection. The compositions determined by neutron reflection and by surface tension measurements in conjunction with the Gibbs equation are in excellent agreement if the prefactor in the Gibbs equation is one, i.e., the surfactant behaves as though it is completely uncharged. At the critical micelle concentration (cmc) the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 21 publications
12
52
0
Order By: Relevance
“…The difference shows that their Langmuir trough method is technically inappropriate for studying soluble surfactant monolayer. For the zwitterionic C12 betaine, a value of 50 Å 2 was however reported by Hines et al [2]. For a similar zwitterionic C12 sulfobetaine, A cmc was reported to be around 47 Å 2 from computer modelling [39].…”
Section: Surface Adsorption From Pure Watermentioning
confidence: 87%
See 3 more Smart Citations
“…The difference shows that their Langmuir trough method is technically inappropriate for studying soluble surfactant monolayer. For the zwitterionic C12 betaine, a value of 50 Å 2 was however reported by Hines et al [2]. For a similar zwitterionic C12 sulfobetaine, A cmc was reported to be around 47 Å 2 from computer modelling [39].…”
Section: Surface Adsorption From Pure Watermentioning
confidence: 87%
“…However, it would be more reliable to believe that the small CMC variation with temperature elevation is the balance between the degree of increase in dehydration at the hydrophilic group which favours micellisation and the extent of disruption of the structured water molecules around the hydrophobic group which disfavours micellisation and would increase the CMC. Others also found that the CMC decrease for C 12 H 25 N + (CH 2 C 6 H 5 )(CH 3 )CH 2 COO − with increasing temperature [46], but for the C12 betaines, little variation in the CMC was detected [2].…”
Section: Temperaturementioning
confidence: 98%
See 2 more Smart Citations
“…They have shown that the adsorption of surfactant on solid hydrophobic compounds is approximately the same as liquid/liquid or liquid/air interfaces (Hines et al 1997). …”
Section: Introductionmentioning
confidence: 99%